Examination of Historical Advancement of Corporate Governance in India– Contemporary Issues and Way Forward - Deepika Kulhari (Qubahan Academic Journal)
In the Era of Globalised world, the importance of Fair Corporate Governance policies has been recognized by different countries. From collapse of Wallpaper Group Coloroll in UK, Enron Scandal in US and Satyam Scam in India, all of these countries have witnessed some of the largest Corporate Scams. With the help of good Corporate Governance Policies, a country can protect its economy and investment made therein. It encourages shareholders to invest in capital market and ensure safety of their investment. In India, the corporate governance and its basic pillars on which governance stands i.e. Transparency, Accountability and Fairness, were introduced through Clause 49. This was done only after it was recommended by the Kumar Mangalam Committee. Yet, subsequently the shocking event of Satyam Scam & other Corporate Governance failure continues to hit Indian economic on various occasions.